Early history of sudden commencement investigation and some newly discovered historical facts - Sano, Yasuharu; Nagano, Hiroshi (History of Geo- and Space Sciences, 2021)
The history of the research on the SC (sudden commencement) of magnetic storms before World War II is studied in this paper. Since geomagnetic research activities before World War II are still not yet fully known, this paper aims to reveal some historical facts related to SC investigation at that time. The first conclusion of this paper is the possible first discoverer of the simultaneity of SC at distant locations. We show that a Portuguese scientist had already pointed it out 16 years earlier than believed. The second conclusion is the role and activities of Aikitu Tanakadate as the reporter of the SC investigation committee of STME (Section of Terrestrial Magnetism and Electricity) and IATME (International Association of Terrestrial Magnetism and Electricity) in the IGGU (International Geodetic and Geophysical Union) or IUGG (International Union of Geodesy and Geophysics). Very little was known about his activities as the reporter of this committee. Our investigation at the Tanakadate Aikitu Memorial Science Museum disclosed how he acted and what he thought of SC, based on his frequent letters to and from other scientists. The third conclusion concerns SC research carried out by Japanese scientists during the period of the Second International Polar Year (1932–1933). Not only Tanakadate but also many other Japanese scientists participated in SC research during this international project. This formed a traditional basis of SC investigation in Japan, prompting a number of Japanese scientists to study SC after World War II.